2017
DOI: 10.1039/c7ra08515j
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in hybrid measurement methods based on atomic force microscopy and surface sensitive measurement techniques

Abstract: This review summaries the recent progress of the combination of optical and non-optical surface sensitive techniques with the atomic force microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 411 publications
(430 reference statements)
0
14
0
1
Order By: Relevance
“…TIRFM has been combined with AFM for correlating specific components at the interface with the topographical data provided by the AFM. 148,149 In 2009, Brown et al applied correlated AFM/TIFRM to investigate self-assembled myosin filaments, which were shown to be asymmetric in physiological buffer. 150 Authors confirmed that the heads of myosin filaments are arranged in a shell of roughly constant thickness around the filament, consistent with having the heads exposed to the outside as required for their actin-binding function.…”
Section: Afm and Near-field Superresolution Microscopy Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…TIRFM has been combined with AFM for correlating specific components at the interface with the topographical data provided by the AFM. 148,149 In 2009, Brown et al applied correlated AFM/TIFRM to investigate self-assembled myosin filaments, which were shown to be asymmetric in physiological buffer. 150 Authors confirmed that the heads of myosin filaments are arranged in a shell of roughly constant thickness around the filament, consistent with having the heads exposed to the outside as required for their actin-binding function.…”
Section: Afm and Near-field Superresolution Microscopy Techniquesmentioning
confidence: 99%
“…156 Correlative AFM/TIRFM schemes often take advantage of AFM force measurement capability to examine sub-cellular variations when mechanical forces are applied. 148,149 AFM micro-and nano-manipulation capabilities have also been exploited with such hybrid microscopy systems. 164,165 Mathur et al described a combination of AFM and TIRFM designed to provide simultaneous mechanical force transmission measurements and focal contact dynamics in human umbilical vein endothelial cells (HUVECs).…”
Section: Afm and Near-field Superresolution Microscopy Techniquesmentioning
confidence: 99%
“…To facilitate ROI relocation, CMI also aims at setting up hardware-fused hybrid setups that inherently co-localize the same ROI due to their joint coordination system. Apart from well-known commercially available PHI scanners (such as PET/CT, SPECT/CT, or PET/MRI), as described in section State-of-the-Art, examples include (i) a variety of hybrid AFM and FM setups [30,171,172], (ii) first implementations of integrated EM-FM setups [111,173], (iii) several combined setups of OCT with photoacoustics or non-linear microscopy [174], and (iv) diverse hardwarebased approaches to combine OI techniques with CT or MRI [175]. Nevertheless, in certain cases, relocation across single modality systems using cross-platform transport beds for CMI may provide superior performance compared to hybrid systems where compromises may have been made in the integration process.…”
Section: Novel CMI Pipelinesmentioning
confidence: 99%
“…In addition, AFM can be combined with other characterization techniques, such as fluorescence microscopy or Raman/IR spectroscopy,t oo vercome its own limitations (e.g.,a bsolute distance or chemical fingerprint determination). [10] An extensive article presenting the history,d evelopment,a nd prospects of high-speed AFM was writtenb y Ando. Francis et al discussed the contribution and versatility of the technique appliedt ob iological and biomedical systems.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Handschuh-Wang et al described, in ac ompactw ay,n ew advancesi nt he combination of opticalt echniques with AFM, explaining their basic principles and pointingo ut different applications. [10] An extensive article presenting the history,d evelopment,a nd prospects of high-speed AFM was writtenb y Ando. [11] Researchers interested in high-vacuum AFM should focus on the detailed article written by Giessibl.…”
Section: Introductionmentioning
confidence: 99%